P3P(Training, Use, and Implementation) of the GO-Turtles Application as a Provider of Turtle Conservation and Ecotourism Services Supporting Conservation Groups - Andri Sahata Sitanggang; R Fenny Syafariani; Febilita Wulan Sari; Lusi melian; Agus Nursikuwagus; Novrini Hasti; Wartika (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
There is a discrepancy in reports between each conservation officer and this causes difficulties in carrying out supervision, resulting in a decrease in the number of turtles and slow ticket service processes. This community service activity aims to help community groups consisting of conservation groups and tourism groups in data management. For conservation groups, it is to facilitate the management of conservation data into computerization. Meanwhile, for tour groups, it is easier to process tickets with scan and print technology. Therefore, the Universitas Komputer Indonesia team will carry out training and mentoring activities for the GO-Turtles desktop and mobile-based application. This application consists of a conservation system and a ticketing system. The method used in the creation and implementation of the application uses a technological approach pattern through discussion/dialogue on the problems that occur using a questionnaire with several questions. This application will also be connected to Scanner technology and automatic Printing technology which consists of registration, mailing, conservation, and ticketing functions. The results of the conservation group's community service activities can be filled in online every day and can be saved in the application, while tourism groups, can use scanner technology and printer technology which produce tickets online and offline, and the result of this activity is the data processing process that has been successfully carried out by conservation and tourism officers